Well productivity controlling factors in crystalline terrains of southeastern Brazil - Neves, Mirna A.; Morales, Norberto (Springer, 2007)
Over the last decades, increasing water demands have fostered research to obtain high well yields in crystalline terrains where, besides the intrinsic properties of rocks, the groundwater flow depends on several factors. The depth of the wells, the lithotypes, the presence and thickness of sedimentary coverings and weathered layers, the landforms, the geological structures, and the effects of tectonic stresses are among the most investigated factors considered as determinant of well productivity. The influence of these factors on productivity of wells that exploit the Crystalline Aquifer System in the Jundiai-River Catchment, southeastern Brazil, is investigated in this work. The largest region of the studied area is located on the Precambrian Basement, partially covered by sedimentary deposits. The results show that the sedimentary deposits and the weathered layer are important for high well yield, but it also depends on the existence of a net of open fractures, in order to maintain high productivity. The sites that have more possibility of occurrence of such structures are the regional shear and fault zones and other minor structures with NW-SE and E-W directions, which characterize areas subjected to transtensional stress related to the neotectonics.
Keywords: crystalline rocks; control factors; tectonics; southeastern Brazil